Treatment patterns of high-dose-rate and low-dose-rate brachytherapy as monotherapy for prostate cancer - Barnes, Justin (J Contemp Brachytherapy, 2019)
PURPOSE: Monotherapy with high-dose-rate (HDR) or low-dose-rate (LDR) brachytherapy are both recommended modalities for prostate cancer. The choice between HDR and LDR is dependent on patient, physician, and hospital preferences. We sought to identify treatment patterns and factors associated with receipt of HDR or LDR monotherapy. MATERIAL AND METHODS: We queried the National Cancer Database (NCDB) for patients with localized low- or intermediate-risk prostate cancer treated with HDR or LDR monotherapy. Descriptive statistics were used to analyze patterns of HDR vs. LDR. Patient characteristics were correlated with HDR vs. LDR using multivariable logistic regression. RESULTS: We identified 50,326 patients from 2004-2014: LDR 37,863 (75.2%) vs. HDR 12,463 (24.8%). Median follow-up was 70.3 months. The overall use of monotherapy declined over time. HDR application declined relative to LDR. In 2004, 27.0% of cases were HDR compared to 19.2% in 2014. Factors associated with increased likelihood of HDR on multivariable analysis included: increasing age (OR: 1.01, 95% CI: 1.01-1.01), cT2c disease (OR: 1.25, 95% CI: 1.11-1.41), treatment at an academic center (OR: 2.45, 95% CI: 2.24-2.65), non-white race (OR: 1.34, 95% CI: 1.27-1.42), and income > $63,000 (OR: 1.73, 95% CI: 1.59-1.88). LDR was more common in 2010-2014 (OR: 0.59, 95% CI: 0.54-0.65), Charlson-Deyo comorbidity index > 0 (OR: 0.89, 95% CI: 0.84-0.95), and for patients receiving hormone therapy (OR: 0.88, 95% CI: 0.83-0.93). No difference in prostate-specific antigen (PSA) or Gleason score and receipt of HDR vs. LDR was observed. Mean overall survival was 127.0 months for HDR and 125.4 for LDR, and was not statistically different. CONCLUSIONS: We observed an overall decrease in brachytherapy (BT) monotherapy use since 2004 for localized prostate cancer. Despite similar survival outcomes, the use of HDR monotherapy declined relative to LDR.